(untitled) (International Journal of Environmental Sciences, 2025)
Background and objectives: Sciatic nerve block is a commonly used technique for providing anaesthesia and analgesia to the lower extremity. Neuraxial blockade as well as general anaesthesia are more frequently used alternative anaesthetic procedures. Traditionally, it is performed using posterior or lateral techniques. However, in some situations where patient positioning is difficult, an anterior approach may be more appropriate [3]. Nonetheless, an Anterior sciatic block is useful in controlling postoperative pain after lower-limb surgeries. Hence, with this study, we aim to assess the efficacy of variable concentrations of Ropivacaine in ultrasound-guided Anterior sciatic nerve block for patients undergoing lower limb surgeries. Methodology: A prospective randomised study was conducted in sixty patients of ASA grade I and II, between the ages of 18 to 75 years, who underwent lower limb surgeries at Adichunchanagiri Institute of Medical Sciences and Research Centre, B. G. Nagara, Mandya, for a period of 18 months. Ultrasound-guided Anterior sciatic nerve block was performed using the anterior approach with the patient lying in the supine position. At the level of the lesser trochanter, the sciatic nerve is imaged approximately. The nerve is typically visualised at a depth of 5-8 cm. Ropivacaine 0.25% 15ml +4mg/ml dexamethasone or 0.5%Ropivacaine 15ml +4mg/ml dexamethasone is given according to randomised assignment. Onset of motor block, onset of sensory block, duration of analgesia, time for rescue analgesia, analgesia quality, and any adverse effects of the Anterior sciatic nerve block were evaluated. Statistical analysis of the data was done using Student-t-test for parametric data and Chi-square test for non-parametric data. Results: The time of perception of pain was considered as the total duration of analgesia, and the mean duration of analgesia was 449.5 ± 17.36 minutes, with a range of 421 to 480 minutes in Group A and 905.43 ± 36.67 minutes, ranging from 840 to 960 minutes in Group B. All the study subjects received rescue analgesia when the VAS score was>4, and the time of receiving 1st rescue analgesia was 525.20 ± 16.65 minutes, ranging from 490 to 559 minutes in Group A and 985.06 ± 35.88 minutes, ranging from 905 to 1040 minutes in Group B. Conclusion: In present, it can be concluded that 0.5% ropivacaine provides superior analgesic efficacy compared to 0.25% ropivacaine in ultrasound-guided anterior sciatic nerve blocks. Satisfactory sensory and motor blockade, with increased duration of analgesia without any adverse effects, with the added advantage of cost effectiveness.